2008
DOI: 10.1186/1743-422x-5-100
|View full text |Cite
|
Sign up to set email alerts
|

Elective caesarean section versus vaginal delivery for preventing mother to child transmission of hepatitis B virus – a systematic review

Abstract: Background: Caesarean section before labor or before ruptured membranes ("elective caesarean section", or ECS) has been introduced as an intervention for preventing mother-to-child transmission (MTCT) of hepatitis B virus (HBV). Currently, no evidence that ECS versus vaginal delivery reduces the rate of MTCT of HBV has been generally provided. The aim of this review is to assess, from randomized control trails (RCTs), the efficacy and safety of ECS versus vaginal delivery in preventing mother-to-child HBV tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
15

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 19 publications
3
70
0
15
Order By: Relevance
“…A large retrospective study of 569 HBeAg-positive mothers showed that the rate of immunoprophylaxis failure was significantly reduced by Cesarean section to 2.1% at 7-12 months after birth, compared with 5.9% associated with vaginal delivery (p<0.017) (20). In addition, a meta-analysis of four randomized trials of 789 pregnant mothers showed that Cesarean section effectively reduces the MTCT of HBV compared to vaginal delivery (10.5 % vs. 28.0%) (21). However, Cesarean section plays no role in reducing intrauterine infection and must be performed before the onset of labor or rupture of membranes in order to be effective (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large retrospective study of 569 HBeAg-positive mothers showed that the rate of immunoprophylaxis failure was significantly reduced by Cesarean section to 2.1% at 7-12 months after birth, compared with 5.9% associated with vaginal delivery (p<0.017) (20). In addition, a meta-analysis of four randomized trials of 789 pregnant mothers showed that Cesarean section effectively reduces the MTCT of HBV compared to vaginal delivery (10.5 % vs. 28.0%) (21). However, Cesarean section plays no role in reducing intrauterine infection and must be performed before the onset of labor or rupture of membranes in order to be effective (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a meta-analysis of four randomized trials of 789 pregnant mothers showed that Cesarean section effectively reduces the MTCT of HBV compared to vaginal delivery (10.5 % vs. 28.0%) (21). However, Cesarean section plays no role in reducing intrauterine infection and must be performed before the onset of labor or rupture of membranes in order to be effective (21).…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the two groups (elective caesarian section versus vaginal delivery) had statistical significance (Relative risk (RR) 0.41, 95% CI 0.28-0.60, P < 0.001). 99 However, methodological concerns including lack of information on randomization procedure, lack of allocation concealment, and lack of blinding, make the role of elective caesarian section for preventing mother to infant transmission of HBV uncertain. More high quality controlled trials are required for assessing the effects of elective caesarian section in comparison to vaginal delivery for preventing mothers to infant transmission of HBV.…”
Section: Natal (Intrapartum) Stage Interventions Caesarian Section Ormentioning
confidence: 99%
“…In addition, elective CS has to be performed before the onset of labor or before the rupture of membranes to achieve effectiveness. 99 At this point, most obstetrical algorithms do not include change in the planned mode of delivery for HBsAgpositive women regardless of HBeAg status or level of viremia. 99 Current available data did not show any association between the risk of transmission and forceps/vacuum extraction during delivery.…”
Section: Natal (Intrapartum) Stage Interventions Caesarian Section Ormentioning
confidence: 99%
“…• Until now it was quite unclear whether the mode of delivery influences the likelihood of HBV transmission as far as passive and active immunization were implied [94][95][96][97][98].…”
Section: Pregnant Women With Hepatitis Bmentioning
confidence: 99%